2014
DOI: 10.1108/medar-08-2013-0032
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing toward student performance in a distance education accounting degree

Abstract: Acknowledgments:The authors would like to thank the University of South Africa for permission to use student data as well as the financial assistance provided in order to assist in completion of the research paper. ABSTRACT PurposeThe objective of this paper is to examine the effects of five determinates of performance in students (N = 677) who completed three years of financial accounting to obtain a Bachelor of Accounting Science (BCompt) degree by distance education through the University of South Africa. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
2
16
0
2
Order By: Relevance
“…In conclusion the mean obtained in the final marks for students who had Accounting prior to university (M=60.5) was higher than the students' mean with no prior Accounting (M=50.7). The outcomes of this study confirm with the outcomes of Papageorgiou and Halabi (2014) and Rankin et al (2003) that prior accounting knowledge was found to be significantly associated with first-year Accounting students' performance. Furthermore correlation between repeated measured was tested between students with and without prior accounting knowledge and marks obtained in three tests (April, June and September) and the November exam.…”
Section: Research Questionsupporting
confidence: 84%
See 3 more Smart Citations
“…In conclusion the mean obtained in the final marks for students who had Accounting prior to university (M=60.5) was higher than the students' mean with no prior Accounting (M=50.7). The outcomes of this study confirm with the outcomes of Papageorgiou and Halabi (2014) and Rankin et al (2003) that prior accounting knowledge was found to be significantly associated with first-year Accounting students' performance. Furthermore correlation between repeated measured was tested between students with and without prior accounting knowledge and marks obtained in three tests (April, June and September) and the November exam.…”
Section: Research Questionsupporting
confidence: 84%
“…Furthermore, this study also emphasises the importance of accounting that could be added to the list as a pre-requisite for the admission requirements to an accounting degree. Previous research confirmed that students' pass rate with no prior accounting knowledge was improved by attending lectures (Baard et al 2010, 142) while other studies confirmed a significant association between students with prior accounting knowledge and students' marks (Rohde and Kavanagh 1996; Farley and Ramsay 1988;Papageorgiou and Halabi 2014;Eskew and Faley 1988). The studies of Uyar andGüngörmüş (2011), Van Rensburg et al (1998) and Rowlands (1988) confirmed that prior Accounting exposure tends to improve student performance.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Factors that influence the academic performance of students, that may prevent students from graduating or extend their degree with a year or longer, have attracted the attention of many researchers; factors such as students' age, gender, attitude, extended curriculum, personality, diversity, transition from secondary to tertiary education and prior academic achievement (Duff 2004;Bergin 2001;Chansarkar and Michaeloudis 2001;Lubbe 2017;Papageorgiou and Halabi 2014;Van Rensburg, Penn and Haiden 1998;Woollacott, Snell and Laher 2013;Duff and Mladenovic 2015;Papageorgiou 2017;Papageorgiou and Callaghan 2018;Steenkamp, Baard and Frick 2009). For some students who enter higher education, career and educational ambitions, individual benefits and quality of learning are the main drivers (Samsuddin, Khairani, Wahid and Sata 2015;Biggs 2003) to academic success.…”
Section: Introductionmentioning
confidence: 99%